Verification of Conjugate Heat Transfer Models in a Closed Volume with Radiative Heat Source; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Maksimov V. I. Vyacheslav Ivanovich (2016, 2016)
Title screen